Pengaruh Keberhasilan Akademik Dan Keaktifan Berorganisasi Terhadap Employability: (Studi Pada Alumni Fakultas Ekonomi Dan Bisnis Universitas Lampung) - Attama Putra, Dicky; Mardiana, Nova; Safitri, Dina (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2025)
This study aims to analyze the influence of academic achievement and organizational activeness on employability among alumni of the Faculty of Economics and Business, University of Lampung. The research employs a quantitative causal design. The population consists of all alumni from 2022–2024, with a total sample of 125 respondents determined using the Slovin formula with a 9% margin of error. Data were collected via an online questionnaire and analyzed using multiple linear regression. The results show that academic achievement has a positive but insignificant effect on employability, while organizational activeness has a positive and significant effect. These findings indicate that active participation in student organizations strengthens interpersonal, leadership, and adaptability skills, which directly contribute to graduates' competitiveness in the job market. The faculty is encouraged to enhance mentoring programs and organizational activities to improve students' career readiness.